Monitoring of Geomagnetic Field Fluctuations with Luminescent Bacteria Photobacterium phosphoreum - Hretskyi, І.O.; Drobot, H.Y.; Pet’ko, B.; Gromozova, O.M.; Kisten, O.G.; Gorgo, Y.P.; Грецький, І.О.; Дробот, Г.Ю.; Петько, Б.; Громозова, О.М.; Кістень, О.Г.; Горго, Ю.П. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
In recent years, one of the important goals is to develop information systems for continuously monitoring the biological impact of the variable geomagnetic field. This problem is of importance from the viewpoint of forecasting such global processes as climate changes as well. Objective. This study is focused on monitoring the intensity of the luminescence of Photobacterium phosphoreum depending on the geomagnetic field fluctuations in an automated registration mode. Pilot studies were performed using the proposed automated system for recording changes in the bioluminescence of P. phosphoreum. Methods. P. phosphoreum UCM B-7071 bacteria were cultured in a liquid nutrient medium. The study of the influence of the geomagnetic field requires simultaneous automated long-term calculations in real time. For this, a complex for continuous cultivation of P. phosphoreum B-7071 bacteria was created. A program for information processing of bacterial luminescence datasets was developed. The data on geomagnetic field fluctuations from the Subbotin Institute of Geophysics NAS of Ukraine (the Subbotin IGPH) were synchronized with the period of registration of bioluminescence changes. Then the two datasets of the variables selected for chosen time intervals were processed. To evaluate the dependence of changes in the bacteria’s luminescence intensity on geomagnetic field fluctuations, the correlation coefficients of the obtained arrays of experimental data were calculated. Results. The results obtained show the sensitivity of the Photobacterium phosphoreum luminescence to fluctuations in the geomagnetic field. The used data sampling method made it possible to average the luminescence intensity values not only with 1-min resolution, but also with 1-hour, 3-hour, and other chosen resolutions. Conclusions. The analysis of changes in the luminescence intensity of P. phosphoreum bacteria due to geomagnetic field fluctuations, with input data being synchronized in time, revealed a positive correlation. Additional analysis is needed to obtain more essential evidence for the bioresponse to the impact of illustrative indicators of geomagnetic field stormy fluctuations. Actually, further analysis of luminescence intensity changes during large natural geomagnetic disturbances or via modeling of their action in the laboratory conditions is needed.